Tiếng Anh giao tiếp dành cho người bán hàng (2011)
Unit 1: Greeting Customers Unit 2: Asking for more information Unit 3: Asking for advice Unit 4: Asking for discounts Unit 5: Bargaining Unit 6: Mistakes about a price Unit 7: How will you be paying? Unit 8: Exchanging Merchandise Unit 9: Making sales on the phone Unit 10: Dealing with an unsatisfied customer